Latifolin protects against myocardial infarction by alleviating myocardial inflammatory via the HIF-1α/NF-κB/IL-6 pathway - Xiao-Xiao Lai; Ni Zhang; Lan-Ying Chen; Ying-Ying Luo; Bin-Yao Shou; Xin-Xu Xie; Rong-Hua Liu (Taylor & Francis Group, 2020)
Context The Traditional Chinese herb medicine Dalbergia odorifera T. Chen (Fabaceae), exerted a protective effect on myocardial ischaemia. Latifolin is a neoflavonoid extracted from Dalbergia odorifera. It has been reported to have the effects of anti-inflammation and cardiomyocyte protection. Objective To investigate whether latifolin can improve myocardial infarction (MI) through attenuating myocardial inflammatory and to explore its possible mechanisms. Materials and methods Left coronary artery was ligated to induce a rat model of MI, and the rats were treated with sodium carboxymethyl cellulose (CMC-Na) or different doses of latifolin (25, 50, 100 mg/kg/d) by oral gavage for 28 days. Serum contents of myocardial enzyme were measured at seven and fourteen days after treatment. Cardiac function, infarct size, histopathological changes and inflammatory cells infiltration was assessed at 28 days after treatment. Western blotting was used to investigate the underlying mechanisms. Results Latifolin treatment markedly decreased the contents of myocardial enzymes, and increased left ventricular ejection fraction (85.27% vs. 59.11%) and left ventricular fractional shortening (62.71% vs. 45.53%). Latifolin was found to significantly reduced infarction size (27.78% vs. 39.07%), myocardial fibrosis and the numbers of macrophage infiltration (436 cells/mm2 vs. 690 cells/mm2). In addition, latifolin down-regulated the expression levels of hypoxia-inducible factor-1α (0.95-fold), phospho-nuclear factor-κB (0.2-fold) and interleukin-6 (1.11-fold). Discussion and conclusions Latifolin can protect against myocardial infarction by improving myocardial inflammation through the HIF-1α/NF-κB/IL-6 signalling pathway. Accordingly, latifolin may be a promising drug for pharmacological treatment of ischaemic cardiovascular disease.